2021
DOI: 10.3389/fsufs.2021.617783
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and Promotion of Resilient Crops for Climate Risk Mitigation and Import Substitution: A Case Analysis of Cassava for South African Agriculture

Abstract: Cassava is an important starchy root crop grown globally in tropical and subtropical regions. The ability of cassava to withstand difficult growing conditions and long-term storability underground makes it a resilient crop, contributing to food security. Historically, small-scale farmers have grown cassava as a minor crop in the far north-eastern part of the country. However, there is an initiative to scale up cassava production, with two discrete areas of interest: large-scale production for industrial starch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 66 publications
0
42
0
Order By: Relevance
“…Cassava roots contain a starch content of 40% higher than rice and 25% more than maize [3]. The importance of cassava for food security, climate risk mitigation, import substitution for industrial starch, livestock feed, and biofuel feed stock to South Africa's economy has been reviewed by Amelework et al [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cassava roots contain a starch content of 40% higher than rice and 25% more than maize [3]. The importance of cassava for food security, climate risk mitigation, import substitution for industrial starch, livestock feed, and biofuel feed stock to South Africa's economy has been reviewed by Amelework et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, South Africa is importing more than 66,000 tons of starch annually [5]. It was reported that cassava starch is preferred in South Africa in terms of imports and it fetches a higher price on the market than maize, potato, or wheat [4]. Hence, grasping the industrial potential of cassava in the starch industry would satisfy local starch demands, avoid computation among staple food commodities, and reduce import volume.…”
Section: Introductionmentioning
confidence: 99%
“…With the approach of global warming concurrent with population growth, nutritious staple foods must be developed using sustainable ingredients from resilient crops, which can thrive within an altered climate. Cassava ( Manihot esculenta ) is a tropical crop that can tolerate a wide range of climatic conditions, including drought, as well as having the ability to grow in areas with low soil fertility, where many other crops are unable to grow [ 1 ]. Cassava yields the highest amount of carbohydrate per cultivation area of any crop [ 2 ], with low investment and irrigation requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Cassava yields the highest amount of carbohydrate per cultivation area of any crop [ 2 ], with low investment and irrigation requirements. It also provides minerals and vitamins, though it is low in protein [ 1 ]. It has an advantage for food security, being able to be stored underground for harvest when required [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation